2015
DOI: 10.7161/anajas.2015.30.3.254-259
|View full text |Cite
|
Sign up to set email alerts
|

A research on determination of factors affecting the artificial insemination of dairy farms: A case study of Van province of Gevaş district

Abstract: ÖZET Suni tohumlama, düşük verimli hayvan ırklarının genetik iyileştirilmesi için tasarlanmış en önemli tekniktir. Çalışmada süt sığırcılığı işletmelerinde, suni tohumlama yaptırma durumuna etki eden başlıca sosyo-ekonomik ve işletmecilik özellikleri belirlenmeye çalışılmıştır. Çalışmanın ana materyalini, Van İli Gevaş ilçesinde süt sığırcılığı üretim faaliyetinde bulunan 81 adet işletmeden toplanan veriler oluşturmaktadır. Suni tohumlama yaptıran ve yaptırmayan işletmelerin kimi değişken ortalama değerleri ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 1 publication
4
8
1
Order By: Relevance
“…It was found that 38.1% of the farmers were aged between 26-36 and the average age was 40.8. In studies conducted in province of Van in Turkey and Uganda, the average age of the farmers was reported to be 45.0 and 44.5, respectively (Kaaya et al, 2005;Gençdal et al, 2015). Thus, it can be said that the results of this study are congruent with the findings of previous studies.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…It was found that 38.1% of the farmers were aged between 26-36 and the average age was 40.8. In studies conducted in province of Van in Turkey and Uganda, the average age of the farmers was reported to be 45.0 and 44.5, respectively (Kaaya et al, 2005;Gençdal et al, 2015). Thus, it can be said that the results of this study are congruent with the findings of previous studies.…”
Section: Resultssupporting
confidence: 87%
“…In this study, the ratio of the farmers who use AI was 85.3% and those who do not use AI was 14.7%. Similarly, the ratio of the farmers using AI was determined as 49%, 50.3%, 54.5%, 75.2% and 56%, respectively, in some studies (Howard and Cranfield, 1995;Aksoy et al, 2011;Özyürek et al, 2014;Gençdal et al, 2015). According to these results, it can be said that the ratio of AI use in the four districts known as the mountain region is higher than the ratio found in previous studies.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations